A Nonaqueous Potassium‐Based Battery–Supercapacitor Hybrid Device. Issue 20 (30th March 2018) - Fan, Ling; Lin, Kairui; Wang, Jue; Ma, Ruifang; Lu, Bingan
Abstract: A low cost nonaqueous potassium‐based battery–supercapacitor hybrid device (BSH) is successfully established for the first time with soft carbon as the anode, commercialized activated carbon as the cathode, and potassium bis(fluoro‐slufonyl)imide in dimethyl ether as the electrolyte. This BSH reconciles the advantages of potassium ion batteries and supercapacitors, achieving a high energy density of 120 W h kg −1, a high power density of 599 W kg −1, a long cycle life of 1500 cycles, and an ultrafast charge/slow discharge performance (energy density and power density are calculated based on the total mass of active materials in the anode and cathode). This work demonstrates a great potential of applying the nonaqueous BSH for low cost electric energy storage systems. Abstract : A low cost nonaqueous potassium‐based battery–supercapacitor hybrid device (BSH) is successfully established with soft carbon as the anode, commercialized activated carbon as the cathode, and potassium bis(fluoro‐slufonyl)imide in dimethyl ether as the electrolyte. This BSH reconciles the advantages of potassium‐ion batteries and supercapacitors, achieving a high energy density, a long cycle life, and an ultrafast charge/slow discharge performance.